Clash of Interests and Geopolitical Rivalry in the Red Sea Region - S. A. Ivanov; E. M. Savicheva; V. P. Titov (Сравнительная политика)
The Red Sea and the Aden Gulf area, where from time immemorial ancient sailors paved trade routes, and the North-East Africa (the Horn of Africa) are rapidly turning into an important strategic region. It's about ensuring free access to the Red Sea and, therefore, to the Suez Canal, that significantly reduces the delivery time and cost of goods, including energy resources. It facilitates and cheapens the trade between Europe and Asia.However, such a strategically important region is extremely unstable and turbulent. Navigation here is carried out, including along several narrow straits, which have been named as “suffocating” and “shock points” of modern geopolitics. We note a trend towards increasing competition in this once “sleepy” region. Arab countries such as Egypt, Saudi Arabia, the UAE are striving to secure their interests here in competition with other Middle Eastern “heavyweights” - Turkey and Iran. Qatar has recently joined the above non-Arab actors.The accelerated dynamics of events leads to changes in the balance of power, which affects politics of non-regional actors - China, the United States and others. This article aims to comprehend the prevailing political realities in the area under consideration, to identify the military-political and trade-economic factors that determine the geostrategic importance of the Red Sea and adjacent territories, to determine the features of relations between the countries of the region, as well as their interaction with non-regional players.